Irradiating patients with a cardiac pacemaker Part II. Guidelines of safe treatment of patients with a pacemaker during radiation therapy – a review of the literature - Ziółkowska, Ewa; Zarzycka, Małgorzata; Wiśniewski, Tomasz; Windorbska, Wiesława; Meller, Aleksandra (Contemporary Oncology/Współczesna Onkologia, 2008)
We observe a continuous rise of the number of patients with a cardiac pacemaker who are exposed to irradiation. There are a lot of publications in which researchers evaluate the influence of ionizing radiation on function of these devices, both in vitro and in vivo , and give recommendations about monitoring patients with pacemakers during radiation therapy. Still there is a lack of official recommendations of proceeding with such patients except general recommendations from the American Association of Physicists in Medicine. Many Polish centres of oncology irradiate these patients with their own procedures. The aim of the study is to give detailed guidelines of the safe treatment of patients with a pacemaker during radiation therapy on the basis of a review of the accessible literature.